The Effect of Medicine Ball Training on Hip Rotational Power to Improve Batting Performance in Baseball Athletes - Fajar Permana Anwar; Yadi Sunaryadi; Dede Rohmat Nurjaya; Mulyana (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of medicine ball training on batting performance in Baseball Labs athletes by emphasizing the role of hip rotational strength. Medicine ball training is a form of strength training that involves rotational and explosive movements, in accordance with the characteristics of the batting motion in baseball. This study uses an experimental method with a one group pretest-posttest design. The research sample consisted of 20 baseball athletes using purposive sampling technique. The instrument in this study used “The O’Donnel Test” with the Funggo Batting Test test item. The sample followed the training program for 16 meetings. Data analysis using the Wilcoxon Signed Rank Test. The results of the analysis showed that there was a significant difference between the pretest and posttest results (p < 0.05), which means that medicine ball training has a positive effect on improving batting results. Thus, this exercise can be used as an effective alternative in the functional strength development program for baseball athletes.